Hyperoxia Is Associated With Poor Outcomes in Pediatric Cardiac Patients Supported on Venoarterial Extracorporeal Membrane Oxygenation*. Issue 4 (April 2016) - Sznycer-Taub, Nathaniel R.; Lowery, Ray; Yu, Sunkyung; Owens, Sonal T.; Hirsch-Romano, Jennifer C.; Owens, Gabe E.
Abstract : Objectives: Patients who require venoarterial extracorporeal membrane oxygenation because of cardiac failure frequently have supranormal blood oxygen tensions (hyperoxia). Recent studies have suggested worse outcomes in patients with hyperoxia after resuscitation from cardiac or respiratory arrests, presumably because of oxidative stress. There are limited data regarding the effect of hyperoxia on outcomes in pediatric patients on venoarterial extracorporeal membrane oxygenation. Design: Retrospective chart review. Setting: Pediatric cardiothoracic ICU. Patients: Cardiac surgery patients less than 1 year old requiring venoarterial extracorporeal membrane oxygenation in the postoperative period from 2007 to 2013. Measurements and Main Results: In 93 infants (median time on extracorporeal membrane oxygenation, 5 d), mortality at 30 days post surgery (primary outcome) was 38%. Using a receiver operating characteristic curve, a mean PaO2 of 193 mm Hg in the first 48 hours of extracorporeal membrane oxygenation was determined to have good discriminatory ability with regard to 30-day mortality. Univariate analysis identified a mean PaO2 greater than 193 mm Hg ( p = 0.001), longer cardiopulmonary bypass times ( p = 0.09), longer duration of extracorporeal membrane oxygenation ( p < 0.0001), and higher extracorporeal membrane oxygenation pump flows ( p = 0.052) as possible risk factors for 30-day mortality. In multivariable analysis controlling for the variables listed above, a mean PaO2 greater than 193 mm Hg remained an independent risk factor for mortality ( p = 0.03). In addition, a mean PaO2 greater than 193 mm Hg was associated with the need for renal dialysis ( p = 0.02) but not with neurologic injury ( p = 0.41) during the hospitalization. Conclusions: In infants with congenital heart disease who are placed on venoarterial extracorporeal membrane oxygenation postoperatively, hyperoxia (defined as a mean PaO2 > 193 mm Hg in the first 48 hr of extracorporeal membrane oxygenation) was an independent risk factor for 30-day mortality after surgery. Future studies are needed to delineate the causative or associative role of hyperoxia with outcomes, especially in children with baseline cyanosis who may be more susceptible to the effects of oxidative stress.